Empowering Indonesian Migrant Workers: Human Rights-Based Legal Protection through Village Regulations and Bilateral Agreements - Farida, Elfia (Journal of Southeast Asian Human Rights, 2025)
This analysis explores the various international and national legal frameworks designed to safeguard migrant workers, emphasizing these protections’ significance for the workers and their families. The optimal legal protection for Indonesian migrant workers and their families can be classified into internal and external. The process encompasses the execution of international accords concerning the safeguarding of migrant workers and their families, the enhancement of the enforcement of Indonesia’s Law on the Protection of Migrant Workers, and the advocacy of Village Regulations designed to shield citizens employed abroad, especially in regions with a significant population of migrant workers. The government ought to enhance the comprehension of human rights among migrant workers and their families. It should also increase public awareness through outreach, dissemination, and campaigns focused on safe and dignified labor migration while empowering and building the capacity of migrant workers and their families. The optimal approach to protection necessitates the formulation of bilateral agreements with the reception countries. These agreements ought to integrate the essential elements of the ICMW.